The language of unknown things: a question triptych - Rodríguez, Juan Sebastián Ballén (Universidad Santo Tomás, Bogotá-Colombia, 2015)
In the history of philosophical anthropology, no other question has defined a dimension for the problematic and paradoxical character that is to be drawn from the question of what it means to belong to mankind. The lines proposed below are complementary readings to those formulated by the metaphysical tradition (Aristotle, Aquinas and Heidegger), the structuralist tradition (Levi-Strauss and Foucault), and the cultural tradition (Protagoras of Abdera and Nietzsche). It belongs to the tradition of transcendental philosophy, but focuses on a work that has been little explored from the anthropologycal point of view and which originally arose from aesthetic concerns. Kant’s Third Critique is the “breeding ground” for the projection of a theoretical approach which I have called “symbolic anthropology” which in turn will become the sounding board for such proposal and evoke the tradition of Philosophical anthropology. An introduction to a philosophy of culture (1944) of neo-Kantian Ernst Cassirer. From Latin America, in a contemporary context, the research of the Mexican philosopher Beuchot will also be taken into account, in particular his provocative proposal for analogue hermeneutics which, in this first study, will be assessed based on a telling and profound book entitled Hermenéutica, analogía y símbolo (2004).